New data on spiders (Arachnida: Aranei) of the plain part of Altai Territory, Russia - Fomichev, Alexander A. (Acta Biologica Sibirica, 2022)
The paper provides a list of 93 spider species collected from the plain part of Altai Territory; of them, 33 species are recorded for the first time and 12 are newly found in West Siberian Plain. Five species of the latter group are illustrated: Euophrys uralensis Logunov, Cutler et Marusik, 1993, Gibbaranea ullrichi (Hahn, 1835), Parasyrisca marusiki Kovblyuk, 2003, Pardosa jaikensis Ponomarev, 2007 and Synema utotchkini Marusik et Logunov, 1995. A new species, Pardosa ogudovi sp. n. (♂♀) is described.